UJI AKTIVITAS ANTIDIARE EKSTRAK DAUN KESUM (Polygonum minus Huds) TERHADAP MENCIT PUTIH JANTAN (Mus musculus): BAHASA INDONESIA - Dian kartikasari; Puspita, Weni; Puspa Sari, Heni; Inderiyani, Inderiyani; Yolanda, Riska (Jurnal Insan Farmasi Indonesia, 2024)
Diarrhea is a clinical symptom of digestive disorders which is characterized by an increase in the frequency of defecation more than usual and repeatedly accompanied by a change in the shape and consistency of the feces to become soft or liquid. The aim of this research is to determine the effect of antidiarrheal activity of extract (Polygonum minus Huds) on male white mice and to find out at what concentration of extract is needed for the antidiarrheal effect on male white mice. This research was carried out by inducing mice with oleum ricini, then giving extract, then observing the time when diarrhea occurred, stool consistency, frequency of diarrhea, and the duration of diarrhea. The results obtained showed that there was a significant difference between the positive control group, 0.25% extract, 0.5% extract and 0.75% extract against the negative control group. This indicates that the three test groups have. Then from these data it can be seen that the 0.25% extract group, 0.5% extract and 0.75% extract had no significant differences from the positive control group. This indicates that kesum leaf extract with concentrations of 0.25%, 0.5% and 0.75% has activity that is close to or similar to the positive group